(untitled) (International Journal of Applied Research in Management and Economics, 2024)
This study examined students’ e-commerce adoption factors using data from an entrepreneurship expo at the College of Business and Management Sciences in 2018. A cross-sectional survey involving 774 students revealed significant predictors of e-commerce adoption. Smartphone ownership and regular internet usage increased adoption (OR = 1.7307, p = 0.043), while exhibitors offering food and beverages saw higher adoption rates (OR = 3.6558, p = 0.047). However, post-purchase reviews, entrepreneurship support participation, and e-commerce application use were associated with lower adoption odds. The findings underscore the shift towards digital models, with smartphones enhancing sales and profitability among university students. This study sheds light on e-commerce adoption drivers among students, emphasizing marketing strategies, internet engagement, and technology accessibility.